2016
DOI: 10.1016/j.expneurol.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Current status of fluid biomarkers in mild traumatic brain injury

Abstract: Mild traumatic brain injury (mTBI) affects millions of people annually and is difficult to diagnose. Mild injury is insensitive to conventional imaging techniques and diagnoses are often made using subjective criteria such as self-reported symptoms. Many people who sustain a mTBI develop persistent post-concussive symptoms. Athletes and military personnel are at great risk for repeat injury which can result in second impact syndrome or chronic traumatic encephalopathy. An objective and quantifiable measure, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 224 publications
(304 reference statements)
0
111
0
1
Order By: Relevance
“…First, the detection of small amounts of biomarkers in blood is often difficult due to their dilution in the large fluid volume that comprises the systemic circulation. 71 Second, there exists a low signal-to-noise ratio because blood interfaces with most organ systems of the body and contains a complex, native cell population. Third, the BBB also remains a challenge because it prevents diffusion of CNS material into the systemic circulation.…”
Section: Blood Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the detection of small amounts of biomarkers in blood is often difficult due to their dilution in the large fluid volume that comprises the systemic circulation. 71 Second, there exists a low signal-to-noise ratio because blood interfaces with most organ systems of the body and contains a complex, native cell population. Third, the BBB also remains a challenge because it prevents diffusion of CNS material into the systemic circulation.…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…71,148 Because axon injury is a widely described result of TBI, myelin basic protein, which is a component of the myelin sheaths of oligodendrocytes and Schwann cells, has also been investigated. Specifically, it has been proposed as a marker of TBI in children because serum levels have been found to reach a peak concentration 48-72 hours after injury and remain elevated for up to 2 weeks.…”
Section: Other Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytoskeletal protein αII-spectrin is present in axons and neuronal presynaptic terminals. During cellular injury it is cleaved to form spectrin breakdown products (SBDPs) (72). While studies in this area are limited, Siman et al identified a subset of mTBI patients with elevated plasma N-terminal αII-spectrin fragment (SNTF), which is an SBDP cleaved by calpain (73).…”
Section: Biomarkers Of Traumatic Neuronal/axonal Injurymentioning
confidence: 99%